Early and Midterm Results of Single-Port Video-Assisted Thoracoscopic Sympathectomy - Apiliogullari, Burhan; Esme, Hidir; Yoldas, Banu; Duran, Melike; Duzgun, Nuri; Calik, Mustafa (The Thoracic and Cardiovascular Surgeon, 2012)
Background Video-assisted thoracoscopic sympathectomy (VATS) is the gold standard for patients with hyperhidrosis of the upper limbs. The primary aim of this retrospective study was to evaluate the midterm outcome and the degree of satisfaction of patients who underwent single-port VATS.Methods Forty three patients diagnosed with hyperhidrosis underwent T3, T4 VATS single-port approach, between January 2009 and May 2011. Early and midterm outcome with particular emphasis on patient satisfaction were collected by hospital chart and telephonic interview.Results The mean follow-up was 14 months. No major perioperative complication occurred except for chylothorax in a case. During the immediate postoperative period, all the patients reported palmar anhydrosis. Compensatory sweating (6.9%) and recurrence of hyperhidrosis (6.9%) are responsible mainly for dissatisfaction. No patients experienced moderate or severe chronic pain.Conclusions Single-port VATS is a feasible and minimally invasive technique with a low incidence of chronic pain for the treatment of hyperhidrosis. A few patients may experience compensatory sweating and recurrence of hyperhidrosis. The degree of patient satisfaction with the midterm surgical results is high.
Keywords: hyperhidrosis; surgery; complications; thoracoscopy/VATS